Initial Characterization of the Chloroplast Genome of Vicia sepium, an Important Wild Resource Plant, and Related Inferences About Its Evolution - Li, Chaoyang; Zhao, Yunlin; Xu, Zhenggang; Yang, Guiyan; Peng, Jiao; Peng, Xiaoyun (Frontiers in Genetics, 2020)
Lack of complete genomic information concerning Vicia sepium (Fabaceae: Fabeae) precludes investigations of evolution and populational diversity of this perennial high-protein forage plant suitable for cultivation in extreme conditions. Here we present the complete and annotated chloroplast genome of this important wild resource plant. V. sepium chloroplast genome includes 76 protein-coding genes, 29 tRNA genes, four rRNA genes and one pseudogene. Its 124,095 bp sequence has a loss of one inverted repeat (IR). The GC content of the whole genome, the protein-coding, intron, tRNA, rRNA and intergenic spacer regions was 35.0%, 36.7%, 34.6%, 52.3%, 54.2%, and 29.2%, respectively. Comparative analyses with plastids from related genera belonging to Fabeae demonstrated that the greatest variation in the V. sepium genome length occurred in protein-coding regions. In these regions, some genes and introns were lost or gained; for example, ycf4, clpP intron, and rpl16 intron deletions and rpl20 and ORF292 insertions were observed. Twelve highly divergent regions, 66 simple sequence repeats (SSRs) and 27 repeat sequences were also found in these regions. Detailed evolutionary rate analysis of protein-coding genes showed that Vicia species exhibit additional interesting characteristics including positive selection of ccsA, clpP, rpl32, rpl33, rpoC1, rps15, rps2, rps4 and rps7, and the evolutionary rates of atpA, accD, and rps2 in Vicia are significantly accelerated. These genes are important candidate genes for understanding the evolutionary strategies of Vicia and other genera in Fabeae. The phylogenetic analysis showed that Vicia and Lens are included in the same clade and that Vicia is paraphyletic. These results provide evidence regarding the evolutionary history of the chloroplast genome.